2016
DOI: 10.1186/s12864-016-2875-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of favorable SNP alleles and candidate genes for traits related to early maturity via GWAS in upland cotton

Abstract: BackgroundEarly maturity is one of the most important and complex agronomic traits in upland cotton (Gossypium hirsutum L). To dissect the genetic architecture of this agronomically important trait, a population consisting of 355 upland cotton germplasm accessions was genotyped using the specific-locus amplified fragment sequencing (SLAF-seq) approach, of which a subset of 185 lines representative of the diversity among the accessions was phenotypically characterized for six early maturity traits in four envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 53 publications
8
83
0
1
Order By: Relevance
“…The SLAF-seq approach was used to genotype the natural population as described in a previous study30, and 691,978 SNPs were identified with call success. A total of 81,675 SNPs were selected for further analyses after excluding the SNPs with more than 10% missing data, a minor allele frequency (MAF) <5%, and an average marker density of 1 SNP per 24.85 kb30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLAF-seq approach was used to genotype the natural population as described in a previous study30, and 691,978 SNPs were identified with call success. A total of 81,675 SNPs were selected for further analyses after excluding the SNPs with more than 10% missing data, a minor allele frequency (MAF) <5%, and an average marker density of 1 SNP per 24.85 kb30.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 81,675 SNPs were selected for further analyses after excluding the SNPs with more than 10% missing data, a minor allele frequency (MAF) <5%, and an average marker density of 1 SNP per 24.85 kb30. To estimate the genetic diversity of natural populations, these SNPs were divided into 26 groups according to chromosome, and the genetic diversity values were calculated for each group.…”
Section: Resultsmentioning
confidence: 99%
“…The co‐located region related to early maturity could easily be used for cotton breeding by recombination and exchange (Figure c). Furthermore, we observed that the candidate genes associated with yield and fibre quality, especially traits that were amenable to selection, such as BW, FP, LP, FL and FS (Figure S11, Table S11), were also located in high‐recombination regions based on previous studies (Su et al ., ; Fang et al ., ; Huang et al ., ; Sun et al ., ; Wang et al ., ; Ma et al ., ). Recombination hot spot regions carrying favourable mutations can be further utilized in important genetic regions (Hartl and Clark, ).…”
Section: Discussionmentioning
confidence: 99%
“…The SLAF-seq strategy, a novel NGS-based method, has been applied widely in de novo SNP discovery and genotyping of large populations [18], such as highdensity genetic map construction of cucumbers [32], candidate genes analysis of cotton [33], and high-quality SNP identification of rapeseed [34]. However, there have been few reports about the application of SLAFseq technology in resistance breeding of livestock, and to our best knowledge, this study is the first report of pig inguinal/scrotal hernias at genome-wide significance using SLAF-seq technology.…”
Section: Discussionmentioning
confidence: 99%